Postal contact with participating children and its impact on response rate: Japan Environment and Children's Pilot Study. Issue 12 (8th August 2016) - Senju, Ayako; Suga, Reiko; Tsuji, Mayumi; Shibata, Eiji; Anan, Ayumi; Yamamoto, Yukiyo; Kusuhara, Koichi; Kawamoto, Toshihiro
Abstract: Background: Communication with participating children and its effect on participation outcome is one of the most important but untouched issues in birth cohort studies. The purpose of this study was to assess the effect of postal communication with the participating preschool children on the response rate to postal questionnaires. Methods: One hundred and five mother–preschool child pairs from the Japan Environment and Children's Study (JECS) pilot cohort were included. During the 6 month study period, letters addressed to the children were enclosed with our biannual questionnaires, and the response rate transition was observed. Additionally, the participants were allocated to two groups. One of these was sent the letter with the individual name of the child at the top, and the other without it. The response rates of the two groups were compared using chi‐squared test. Parents' impressions of the letters and the changes in their motivation to complete the questionnaires were surveyed using an evaluation form. Results: The overall response rate was 83.8%, which was lower than the previous survey period. Response rate was not significantly different between the two letter types. The duration before questionnaire return was not changed. Despite their favorable impression based on parent evaluation, the letters were not associated with the parents' motivation to respond. Conclusion: Letters to participating preschool children had no effect on response rate, but the long‐term impact of its favorability still remains to be evaluated. A similar trial at later ages may be more effective.